Green Products in the Implementation of a Green Economy: An Analysis of Their Impact on Consumption Expenditure - Sindy Marchelia Putri; Muh. Syaukin Muttaqin; Susilowati Susilowati; Ubaid Aisyul Hana; Agam Anantama (Journal of Business Improvement, 2024)
The purpose of this study is to analyze the impact of implementing a green economy through the use of green products, focusing on their effect on consumption expenditure. The respondents consist of 12 informants who are members of the Bumi Ijo group. The study shows that the implementation of a green economy through the use of green products aligns with the objectives of a green economy, as users consciously choose green products to protect the environment and reduce issues related to plastic waste, as well as because green products are more durable. The impact of green products on expenditure is positive, as they serve as alternatives to conventional or factory-made products that can be reused multiple times, despite the higher initial cost